Comparison of methods for evaluating bond strength between concrete substrate and repair materials - Nurulnizam , Mohamed (2013)
Placing freshly mixed concrete against old existing concrete is a point of interest in repair applications, and can be sometimes a vital issue. Unless good bond is ensured at the interface, the concrete section may become improper and sometimes unsafe. An experimental study was performed to investigate the effect of testing methods on bond strength between concrete substrate and repair material. 27 numbers of sample with different dimension were prepared according to different type of testing. Sample with dimension of 150x150x150 mm cubes were required for spliting test. The cubes is constructed into two parts as old substrate concrete and repair material with a size of base size 75x150 mm and a height of 150mm. In the Bi-Surface shear method, the repair material constitutes one third of the samples which means the prisms with a base size of 100x150 mm and a height of 150 mm are cast as old or substrate concrete. Then the repair materials are cast in prisms with a base of 1 50x50 mm and a height of 150 mm and are bonded to the concrete substrate. Slant Shear Test samples were lOOxlOOx400 mm and it is cut at angle 60° to their cross sectional axis whereas the old substrate designed with a base size of lOOxlOOmm and height 1 13.5mm as well as the repaired material samples. Steel wire brush were rub to bonding surface in order to produce different surface roughness. The estimated amplitude of low roughness was 3-4 mm and using a similar approach, the high-roughness was roughened to amplitude of 7-8 mm. After two weeks, the new concrete was added to the substrate concrete. Splitting prism test, BiSurface direct shear test and Slant shear tests were performed to evaluate the bond strength at age 7 days, 14 days and 28 days The results shows sample with high roughness surface were produce more conpressive strength in all type of testing. Hence, direct shear test was develop greater comprasive strength compare to spliting prism test and slant sheat test.